Inflammation Downregulates UCP1 Expression in Brown Adipocytes Potentially via SIRT1 and DBC1 Interaction - Nøhr, Mark K. (Int J Mol Sci, 2017)
Brown adipose tissue thermogenesis at the cost of energy is not only important for the development of obesity, but also possesses great promise in anti-obesity treatment. Uncoupling protein 1 (UCP1) expression has been reported to be under control of the intracellular deacetylase SIRT1. Here, we investigated the effect and mechanism of inflammation and sirtuin-1 (SIRT1) activation on the induction of thermogenic genes in immortalized brown adipocytes incubated with LPS or IL1β and mice with elevated inflammatory tone. In vitro stimulation of brown adipocytes with dibutyryl cyclic adenosine monophosthate (dbcAMP) reduced the expression of deleted in breast cancer-1 (Dbc1) (SIRT1 inhibitor) and increased the Ucp1 expression. Silencing of SIRT1 attenuated dbcAMP induction of Ucp1. In contrast, IL1β increased the expression of Dbc1 and greatly reduced the induction of Ucp1. Similarly, in vivo studies revealed decreased expression of Ucp1 in brown adipose tissue (BAT) in mice chronically infused with LPS. Resveratrol, a known SIRT1 activator, partly rescued the Ucp1 downregulation by inflammation in both the cell cultures and mice. Here, we describe how the expression of Ucp1 in BAT is controlled via SIRT1 and is reduced under inflammation and can be rescued by SIRT1 activation by resveratrol. We suggest the reduced UCP1 expression under inflammation is mediated by the increased expression of DBC1, which inhibits SIRT1 activity.